Evaluation of research in forest regeneration in Finland - Suomen Akatemia (Suomen akatemia, 1988)
Academy of Finland, Research Council for Agriculture and Forestry. The final report of the Committee for Evaluation of Research in Forest Regeneration in Finland. The committee was unanimous in the stated conclusions. A. M. Fletcher, chairman, F. Bergman, E. Donaubauer, H.F. Kaiser, H. Schmidt-Vogt, R.W. Tinus. Coordinator of the evaluation: professor Seppo Kellomäki, University of Joensuu. The secretary of the evaluation: Dr. Pasi Puttonen, University of Helsinki.
Metsänuudistamistutkimuksen arviointi
Keywords: forest regeneration; metsänuudistus; arviointi